Consequences and management of sleep-wake rhythm disorders resulting from social jetlag and nightshifts - Anna Jargieło; Karolina Kosieradzka; Dominik Adamowicz; Justyna Stańczyk; Inga Łopuszyńska; Astrik Meliksetian; Alicja Wosińska; Dorota Pazik; Katarzyna Kosecka; Patryk Rudziński (Kazimierz Wielki University, 2023)
Our day to night cycle is ruled by a social, biological and sun clock. The social clock being a local time is aligned with others' lives. The biological clock (circadian time) that controls our physiology and the sun clock that defines natural light and darkness. Social jetlag refers to the misalignment between local and circadian time. This term is usually used in reference to travels to places in different time zones. Nevertheless, it is worth noticing that "jetlag" also applies to people working in a medical industry such as doctors, nurses, paramedics, and others involved in an on-call work. Thus, I would like to look closer to the physiology of social jetlag and to analyze its implications.